(3OhZhd(B... (3h GdLRGFQ (B:s (3CLOGK(B- (3bVGjG(B- (3TgGOGJ (B/s - (3YHGS, eMeOs ((3GdLRGFQ (B:s (3OGQ gheg ddWHGYI h GdfTQ ,s, 2011)
(3dbO YHG GdLfQGd GdGMJjGWj GdGSJQGJjLj ddbhGJ GdaQfSjI h RL Hg aj eYQcI GdQUI GdGNjQI ddGMJaGX dGLRGFQ aQfSjI dcf HOhf fJjLI dGf GMJjGWj GdTYH GdLRGFQj cGf Gbhi eYfhjG HaVd YOGdI bVjJg h GjeGfg GdQGSN HMbhbg GdhWfjIs
Keywords: (3GdKhQIs; (3GdLRGFQ OhZhds; (3aQfSGs; (3JGQNs